Antimicrobial Peptide Loss, Except for LL-37, is not Characteristic of Atopic Dermatitis - Szabó, Lilla; Kapitány, Anikó; Somogyi, Orsolya; Alhafez, Iman; Gáspár, Krisztián; Palatka, Réka; Soltész, Lilla; Törőcsik, Dániel; Hendrik, Zoltán; Dajnoki, Zsolt; Szegedi, Andrea (Acta dermato-venereologica, 2023)
Atopic dermatitis is an inflammatory skin disease characterized by significant permeability barrier damage. Regulation and maintenance of permeability and antimicrobial skin barriers are strongly connected. There is a lack of comprehensive studies of the expression of all 5 major antimicrobial peptide functional groups in atopic dermatitis. The aim of this study was to investigate the major antimicrobial peptide functional groups in lesional atopic dermatitis, non-lesional atopic dermatitis, and healthy control samples, using real-time quantitative PCR and immunohistochemistry. Lesional psoriatic skin was also examined as a diseased control. No differences in mRNA levels were detected between non-lesional atopic dermatitis and healthy control skin, and, at the protein level, the only change was the significantly decreased LL-37 in non-lesional atopic dermatitis. In lesional atopic dermatitis, several antimicrobial peptides were significantly altered at the mRNA level, while, at the protein level, all antimicrobial peptides were significantly upregulated or unchanged, except for LL-37, which decreased, compared with healthy controls. Antimicrobial peptides were similarly elevated in lesional atopic dermatitis and lesional psoriatic skin, with somewhat higher expression in lesional psoriatic skin, except for LL-37. In conclusion, LL-37 was the only antimicrobial peptide that was impaired in both non-lesional and lesional atopic dermatitis, highlighting its potential pathogenetic or exacerbating role in the initial stages of the disease.